Systematic Review on Treatment and Outcomes of Tuberculous Peritonitis in Patients on Peritoneal Dialysis - Chau Wei Ling; Kamal Sud; Ronald L. Castelino; David W. Johnson; Trevor H.Y. Tan; Vincent W. Lee (Kidney International Reports)
Introduction: Peritoneal dialysis (PD)-associated peritonitis due to tuberculosis (TB) is associated with poor outcomes and optimal treatment strategies for this condition remain unknown. Our study aimed to: (i) systematically review the published literature on peritonitis caused by Mycobacterium tuberculosis in patients on PD and (ii) review cases of peritonitis due to M tuberculosis in patients on PD reported in Australia and New Zealand to determine the epidemiology, management strategies, and outcomes of this condition. Methods: A literature search of Medline, Scopus, Embase, ClinicalTrials.gov, Cochrane CENTRAL Register of Controlled Trials and Google Scholar for articles published from inception date to June 2022 was conducted. To be eligible, articles had to describe patient characteristics, initial anti-TB therapy, and treatment outcomes in all patients on PD with peritonitis caused by M tuberculosis. Data from the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry of patients on PD who developed peritonitis due to M tuberculosis between September 2001 and December 2020 were included and analyzed. Results: The systematic literature review identified 70 case studies (151 patients) and 8 cohort studies (97 patients), whereas the ANZDATA Registry identified 17 cases of peritonitis due to M tuberculosis. Overall, in patients diagnosed with peritonitis due to M tuberculosis, the rates of PD catheter removal and permanent transfer to hemodialysis (HD) were numerically higher in the ANZDATA Registry cases (82%) than in the case studies (23%) and cohort studies (20%). Observed all-cause mortality rates were also higher as observed in the case studies (33%) and cohort studies (26%) than in the ANZDATA Registry cases (6%). Conclusion: Tuberculous peritonitis is uncommon in patients on PD and is associated with poor outcomes. Prospective studies are warranted to study the effect of retaining PD catheters after M tuberculosis infection on patient outcomes.